Docket Control in the Apex Court Exercising Constitutional Review - Kumar, B Muthu (Christ University Law Journal, 2021)
Globally, there was a dramatic and disproportionate increase in caseloads in the second half of the twentieth century due to the expansion of human rights jurisprudence and legal awareness among citizens. This in turn, affected the quality of justice in the Apex Court of every country involved in the process of constitutional review. It was found that there cannot be any generalization in designing a Constitutional Court and it all depended on the constitutional and legal history of that particular nation. In many countries, the legislature and executive brought timely reforms to keep the Apex Court free from backlogs, but some countries, even today, are reeling under the pressure of unresolved cases. India is one among them and of late, the discussion about the National Court of Appeal (NCA) as a solution to this problem has gained momentum. This paper analyses the feasibility of establishing the NCA, along with measures that can be adopted by India, in tackling the mounting arrears of cases in Courts, following the American model of review such as U.S., Canada, Japan, and Brazil.